A study on clinicoradiological correlation in patients with intrauterine contraceptive device - Divangini Yadav; Rachna Chaurasia (Asian Journal of Medical Sciences, 2024)
The aim of this study was to present the spectrum of radiological findings in patients with intrauterine contraceptive device (IUCD). The study was conducted over a period of 14 months (June 2022–August 2023) in the Department of Radiodiagnosis, M.L.B. College, Jhansi. A prospective study was conducted in the Department of Radiology in MLB Medical College Jhansi in 120 cases with IUCD, referred from various departments. These patients were primarily evaluated on transabdominal and transvaginal sonography (3D, 4D) (ultrasound machine-Medison sono Ace-X8, Vivid T8, and Hitachi Aloka SSDF-31), which is the first-line imaging for the evaluation of IUCD position. Out of 120 cases, in 100 cases, findings were confirmed on USG and the rest cases require further radiological modalities such as X-ray, CT scan, and MRI which were used accordingly the presenting symptoms of the patient and findings of ultrasound. As in one of our case, X-ray pelvis has shown completely inverted IUCD.